The Perspective of Therapeutic Antibody Marketing in Iran: Trend and Estimation by 2025 - Monireh Golpour; Pouya Vatanpour; Mina Amini; Majid Saeedi; Nasim Hafezi; Alireza Rafiei (Hindawi Limited, 2021)
Background. Monoclonal antibodies with high efficiency and specificity are one of the best strategies to diagnose and treat a variety of diseases such as cancer, autoimmunity, and inflammatory diseases. The market for monoclonal therapeutic antibodies (MTAs) has grown dramatically in the past decade. Objective. Given the importance of these issues, developing countries spend a high cost on importing or producing MTAs annually. This study intends to examine the market of monoclonal therapeutic antibodies in Iran and predict the future growth rate of this market using the obtained data. Methods. Data on the status of MTAs in the country (from 2008 to 2018) were obtained from the Food and Drug Deputy of Mazandaran University of Medical Sciences. The market status of MTAs was studied based on the dosage forms, application, and price. Then, the market outlook was predicted up to year 2025. Results. The results showed that 58.8% of all MTAs were humanized, and 86% of all antibody-based drugs were used to treat cancer. Sales of MTA-based medications will reach $454 million by 2025 and are projected to grow significantly in the future. Conclusion. Given the increasing technology of the production of MTAs and their use in targeted therapies worldwide, their consumption market in Iran is expected to grow significantly.